Relationship between the quality of orthodontic treatment and patient satisfaction in patients attended at Universidad Santo Tomás from 2018 to 2019 (Revista Nacional de Odontología, 2020)
Introduction: The increasing orthodontic service demands high-quality outcomes so the patient could be satisfied with the results, but scarce studies are addressing this topic. Objective: To assess the relationship between the quality of orthodontic treatment outcomes and patient satisfaction at an Orthodontic Clinic in a Colombian university. Methods: An observational cross-sectional study was conducted with a sample of 67 patients who completed their orthodontic treatment between February 2018 and June 2019. Satisfaction was assessed by a questionnaire consisting of 17 items. The quality of the orthodontic treatments was established with post-treatment study models and panoramic radiographs that were analyzed according to the eight criteria of the Objective Grading System (OGS) generated by the American Board of Orthodontics. Frequencies and proportions for qualitative variables and measures of central tendency and dispersion for quantitative ones were calculated. Chi-square test, Fisher exact test, and Pearson correlation coefficients were used as appropriate. P
Keywords: orthodontics; patient satisfaction; standards; quality of health care [MeSH]